Natural Intra- and Interclade Human Hybrid Schistosomes in Africa with Considerations on Prevention through Vaccination - Ursula Panzner; Jerome Boissier (Microorganisms, 2021)
Causal agents of schistosomiasis are dioecious, digenean schistosomes affecting mankind in 76 countries. Preventive measures are manifold but need to be complemented by vaccination for long-term protection; vaccine candidates in advanced pre-clinical/clinical stages include Sm14, Sm-TSP-2/Sm-TSP-2Al®, Smp80/SchistoShield®, and Sh28GST/Bilhvax®. Natural and anthropogenic changes impact on breaking species isolation barriers favoring introgressive hybridization, i.e., allelic exchange among gene pools of sympatric, interbreeding species leading to instant large genetic diversity. Phylogenetic distance matters, thus the less species differ phylogenetically the more likely they hybridize. PubMed and Embase databases were searched for publications limited to hybridale confirmation by mitochondrial cytochrome c oxidase (COX) and/or nuclear ribosomal internal transcribed spacer (ITS). Human schistosomal hybrids are predominantly reported from West Africa with clustering in the Senegal River Basin, and scattering to Europe, Central and Eastern Africa. Noteworthy is the dominance of Schistosoma haematobium interbreeding with human and veterinary species leading due to hybrid vigor to extinction and homogenization as seen for S. guineensis in Cameroon and S. haematobium in Niger, respectively. Heterosis seems to advantage S. haematobium/S. bovis interbreeds with dominant S. haematobium-ITS/S. bovis-COX1 profile to spread from West to East Africa and reoccur in France. S. haematobium/S. mansoni interactions seen among Senegalese and Côte d’Ivoirian children are unexpected due to their high phylogenetic distance. Detecting pure S. bovis and S. bovis/S. curassoni crosses capable of infecting humans observed in Corsica and Côte d’Ivoire, and Niger, respectively, is worrisome. Taken together, species hybridization urges control and preventive measures targeting human and veterinary sectors in line with the One-Health concept to be complemented by vaccination protecting against transmission, infection, and disease recurrence. Functional and structural diversity of naturally occurring human schistosomal hybrids may impact current vaccine candidates requiring further research including natural history studies in endemic areas targeted for clinical trials.